Provision of Public Housing in Jakarta - Nina Nurdiani (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Public housing is a residential provided by the government for the lower-middle class in city, to be owned. Since 2007, public housing in Jakarta has been built in the form of multi-storey housing (Rusunami). Rusunami is still regarded as one of the best alternatives for the provision of public housing in Jakarta, since the land in the city is very limited and the population is increasing. However, in the development of Rusunami, the displacement of residential units in rusunami is still happening until now. It is necessary to study how the provision of rusunami in Jakarta, whether it meets the needs and target hosts. The study was conducted using a descriptive method which studied provision of rusunami, and other secondary data regarding occupants. The study shows that the increasing number of residential units at rusunami has not covered the needs of residential in Jakarta for the lower-middle class. Occupants in rusunami are generally middle-income families. This condition indicates that the number of residential units and the fulfillment of target criteria at rusunami in Jakarta are still lacking.